Capsaicin-loaded solid lipid nanoparticles: design, biodistribution, in silico modeling and in vitro cytotoxicity evaluation. (3rd December 2020) - Kunjiappan, Selvaraj; Sankaranarayanan, Murugesan; Karan Kumar, Banoth; Pavadai, Parasuraman; Babkiewicz, Ewa; Maszczyk, Piotr; Glodkowska-Mrowka, Eliza; Arunachalam, Sankarganesh; Ram Kumar Pandian, Sureshbabu; Ravishankar, Vigneshwaran; Baskararaj, Suraj; Vellaichamy, Sivakumar; et al.
Abstract: Lower doses of capsaicin (8-methyl- N -vanillyl-6-nonenamide) have the potential to serve as an anticancer drug, however, due to its pungency, irritant effect, poor water solubility and high distribution volume often linked to various off-target effects, its therapeutic use is limited. This study aimed to determine the biodistribution and anticancer efficacy of capsaicin loaded solid lipid nanoparticles (SLNs) in human hepatocellular carcinoma in vitro . In this study, SLNs of stearic acid loaded with capsaicin was formulated by the solvent evaporation-emulsification technique and were instantly characterized for their encapsulation efficiency, morphology, loading capacity, stability, particle size, charge and in vitro drug release profile. Synthesized SLNs were predominantly spherical, 80 nm diameter particles that proved to be biocompatible with good stability in aqueous conditions. In vivo biodistribution studies of the formulated SLNs showed that 48 h after injection in the lateral tail vein, up to 15% of the cells in the liver, 1.04% of the cells in the spleen, 3.05% of the cells in the kidneys, 3.76% of the cells in the heart, 1.31% of the cells in the lungs and 0% of the cells in the brain of rats were determined. Molecular docking studies against the identified targets in HepG2 cells showed that the capsaicin is able to bind Abelson tyrosine-protein kinase, c-Src kinase, p38 MAP kinase and VEGF-receptor. Molecular dynamic simulation showed that capsaicin-VEGF receptor complex is highly stable at 50 nano seconds. The IC50 of capsaicin loaded SLNs in HepG2 cells in vitro was 21.36 μ g × ml −1 . These findings suggest that capsaicin loaded SLNs are stable in circulation for a period up to 3 d, providing a controlled release of loaded capsaicin and enhanced anticancer activity.